Tar formation influence on fixed bed air-blown biomass gasification process efficiency - I. G. Donskoy (Известия высших учебных заведений: Проблемы энергетики)
The paper is devoted to reduced biomass gasification tar formation model. According to this model, fixed volatiles part escapes fuel in the form of tars. Tar content influence on the cold gas efficiency is analyzed. It is shown that tar formation in is key process that determines gasification process efficiency.